Shifting financial flows to low-income countries: From official aid to private finance - Lotte Thomsen (Danish Institute for International Studies (DIIS), 2008)
Within the last decades, the share of government aid in overall external financial flows to developing countries has decreased. It is estimated that between 75 and 85% of all current financial flows to developing countries derive from a variety of private sources, including remittances, investment, commercial loans and charity, compared to some 65% in 1990. Similarly, it has been estimated that total private flows reached 647 billion USD in 2006, which is roughly four times their level in the 1980s. This may imply a diminished or different role for official financing from 'traditional' donors, at least in relative terms. This paper aims to provide an overview of recent and current changes in financial flows to developing countries. First, it explores the different types of financial flows to developing countries aiming at determining their recent and current importance. Second, to the extent possible, the tendencies described are broken down to particular developing countries or regions, and attention is also paid to whether or not the particular types of flows benefit certain sectors over others. Third, the described tendencies are compared, while their impact on developing countries is briefly discussed and concluded.
Keywords: 330; Entwicklungshilfe; Private Entwicklungshilfe; Direktinvestition; Welt